Smart driving assistance system for mining operations in foggy environments - Swades Kumar Chaulya; Monika Choudhary; Naresh Kumar; Vikash Kumar; Abhishek Chowdhury (Discover Electronics)
Abstract Environmental conditions such as fog and rain are among the most challenging scenarios for drivers of heavy vehicles in open-pit mines. This paper proposes an efficient camera-based driving assistance system to improve image quality for operators of heavy vehicles for safe driving in open-pit mines. The system incorporates image processing algorithms and technologies such as proximity radar and global navigation satellite system to provide multi-stage safety features while driving. Finally, the screen fitted in the dashboard is forward-facing to the operator's seat and displays the final output. The efficacy of the developed system was assessed through its implementation in open-pit mining environments with visibility range of 5 m during dense fog. The system improves the visibility range to around 30–40 m, whereas the unaided eye can only see about 5 m in extremely dense fog conditions at the mine site. The average values of contrast, structural similarity index measure, peak signal-to-noise ratio, visual information fidelity, and universal quality index for the tested images were 0.92, 0.52, 19.42 dB, 0.83, and 0.49, respectively. In image processing under dense fog where visibility is below 5 m, typical performance standards are around 0.9 for contrast, above 0.5 for structural similarity index measure, over 20 dB for peak signal-to-noise ratio, over 0.5 for visual information fidelity, and more than 0.5 for universal quality index. Thus, the test results indicate that the proposed image enhancement algorithm produced significantly improved images, proving its effectiveness in extremely low visibility situations. Additionally, the object detection model demonstrated an accuracy of 88%, indicating satisfactory performance of the system in foggy conditions. Consequently, the system can be safely employed in open-pit mining operations, allowing for the continuation of activities even in foggy conditions.